Spectrum of Morphologic Changes in Histopathological Specimen of Gallbladder in a Tertiary Care Hospital - Karim, Syeda Noorjahan; Nowsher, Md Neaz; Rahman, Shamim (Mediscope, 2022)
Background: Diseases of gallbladder are incidentally found and when symptomatic, present with sign and symptoms of cholecystitis and cholelithiasis. Routine examination of gallbladder both grossly and microscopically shows many interesting findings. Aim: The aim of the study was to observe and analyze the diverse morphological and histopathological features of gallbladder specimens following cholecystectomy procedure. Methods: This cross-sectional study was carried out at the Department of Pathology, Gazi Medical College, Khulna; from April 2019 to March 2021 and the sample size was 62. After routine tissue processing and H/E staining all the slides were thoroughly examined under light microscope stains to confirm the diagnosis as well as to evaluate histopathologic characteristics. The data was tabulated and statistical analysis was performed. Results: Out of 62 cases 30.64% samples belonged to age 26-35 years and the mean age was 44.32 years. 69% patients were female with a female to male ratio 2.26:1. Histologically, majority of the cases (54.83%) were diagnosed as chronic cholecystitis, followed by chronic cholecystitis with cholelithiasis (14.51%). Total 8 (12.91%) patients were found to have carcinoma of gallbladder with 50% of them belonging to grade I. Conclusion: Predominance of female gender in gallbladder ailment is clear from this study. Cholecystitis is the most common gallbladder disease. Microscopy varieties of histomorphological changes, including metaplasia and precursor changes are suggestive of high risk for gallbladder malignancy. Therefore, prompt detailed histopathological analysis of the cholecystectomy specimens will help to confirm the benign nature of the disease or to detect any precursors of malignancy. Mediscope 2022;9(1): 1-4